The Study of Implementation and Adaptation Processes of Innovative Organization and Economic Management Mechanisms for the Activity of Municipal Educational Institutions - Saktoev, Vladimir; Vanchikova, Elena; Slepneva, Ludmila; Bulatova, Nadezda; Khaltaeva, Svetlana (International Journal of Economics and Financial Issues, 2015)
The article deals with implementation and adaptation processes of innovative organization and economic management mechanisms over the activity of municipal educational institutions in Ulan-Ude. There was carried out a retrospective analysis, how the managers of municipal educational institutions perceive the implementation of outsourcing and franchising into the activity. The analysis of perception was carried out as per two aspects: according to the level of current knowledge and according to the degree of acceptance and expectation from the implementation of organization and economic management mechanisms. The possibilities of outsourcing and franchising implementation in municipal educational institutions are considered. Keywords: Innovations, management of educational institution activity, outsourcing, franchising, inquiries of managers, municipal educational institutions. JEL Classifications: I25, I28, O31, O32